Adequate fire safety for structural steel elements based upon life-time cost optimization. (March 2021) - Hopkin, Danny; Fu, Ian; Van Coile, Ruben
Abstract: Structural fire safety requirements implicitly balance up-front investments in materials (protection or element sizing) with improved performance (loss reductions) in the unlikely event of a fire. For traditional prescriptive fire safety recommendations, the underlying target safety levels are not clear to the designer, nor is the associated balancing of risk and investment costs. It is discussed that traditional (structural) fire safety design is deterministic, with the safety foundation premised upon the collective experience of the profession. However, it is noted that building forms are increasingly uncommon in nature, due to material choice, height, failure consequences, etc. Within the framework presented in PD 7974–7:2019 there is an expectation that probabilistic risk assessment (PRA) methods be employed to demonstrate adequate safety for cases where the collective experience of the profession cannot be called upon to guide design approaches. In doing so, any design must be demonstrated to be tolerable to society, and the residual risk as low as is reasonably practicable (ALARP). In support of the PD 7974–7:2019 framework, the paper assesses the failure probabilities of isolated steel elements in function of insulation thickness, utilization, load ratio and (mean) fire load. In support of a generalized definition of target safety levels for structural fire safety engineering, optimum target safety levels for insulated steel beams are then determined as a function of the fire characteristics by applying life-time cost optimization (LCO) techniques. The LCO results in an assessment of the optimum investment level as a function of the fire, and damage and investment cost parameters characterizing the building. It is intended that the current contribution can be a steppingstone towards rational and validated reliability targets for performance-based design (PBD) in structural fire safety engineering. Highlights: Probabilistic methods are central to demonstrating adequate safety for uncommon structures. Reliability based methods underpin ambient temperature design but are not widely adopted in fire safety applications. Fragility curves for protected steel beam elements are computed. Fragility curves indicate failure probability in function of mean fire load, insulation thickness, load ratio & utilization. The fragility curves are applied in life-time cost optimization studies to determine optimal safety targets.